2004
DOI: 10.1105/tpc.104.023960
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar Sulfate Transporters Are Essential Determinants Controlling Internal Distribution of Sulfate in Arabidopsis

Abstract: Uptake of external sulfate from the environment and use of internal vacuolar sulfate pools are two important aspects of the acquisition of sulfur for metabolism. In this study, we demonstrated that the vacuolar SULTR4-type sulfate transporter facilitates the efflux of sulfate from the vacuoles and plays critical roles in optimizing the internal distribution of sulfate in Arabidopsis thaliana. SULTR4;1-green fluorescent protein (GFP) and SULTR4;2-GFP fusion proteins were expressed under the control of their own… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
250
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 289 publications
(258 citation statements)
references
References 44 publications
(72 reference statements)
5
250
0
3
Order By: Relevance
“…A similar up-regulation of sulfate transporters as well as of genes involved in sulfate assimilation (Leustek et al, 1994;Gutierrez-Marcos et al, 1996;Setya et al, 1996) and Cys synthesis (Hatzfeld et al, 2000;Kawashima et al, 2005) was observed in earlier studies where plants were subjected to S deficiency (Takahashi et al, 1997(Takahashi et al, , 2000Yoshimoto et al, 2002;Maruyama-Nakashita et al, 2003, 2005Kataoka et al, 2004). Thus, selenate may be perceived by the plant as S deficiency, or even cause deficiency of certain S-containing metabolites.…”
Section: Discussionmentioning
confidence: 54%
“…A similar up-regulation of sulfate transporters as well as of genes involved in sulfate assimilation (Leustek et al, 1994;Gutierrez-Marcos et al, 1996;Setya et al, 1996) and Cys synthesis (Hatzfeld et al, 2000;Kawashima et al, 2005) was observed in earlier studies where plants were subjected to S deficiency (Takahashi et al, 1997(Takahashi et al, , 2000Yoshimoto et al, 2002;Maruyama-Nakashita et al, 2003, 2005Kataoka et al, 2004). Thus, selenate may be perceived by the plant as S deficiency, or even cause deficiency of certain S-containing metabolites.…”
Section: Discussionmentioning
confidence: 54%
“…Biochemical characteristics together with distinct patterns of gene expression and protein localization indicate that different sulfate transporters fulfill different roles in plants, including high-affinity uptake of soil sulfate into roots, translocation in vascular tissues, and cell-to-cell transfer of sulfate in leaves and seeds (Hawkesford, 2003). Although some plant sulfate transporters are located in the plasma membrane (Kataoka et al, 2004a), at least one has been found elsewhere, on the tonoplast (Kataoka et al, 2004b). Genetic evidence reinforces the notion that plant sulfate transporters have become specialized during evolution, although a certain level of redundancy remains.…”
Section: Discussionmentioning
confidence: 99%
“…Examples are the outward potassium channel SKOR (Gaymard et al, 1998), the effluxtype boron transporter BOR1 (Takano et al, 2002), the tonoplast sulfate transporters SULTR4;1 and SULTR4;2 (Kataoka et al, 2004b), the plasma membrane sulfate transporters, SULTR2;1 (A) Low-affinity nitrate uptake activity. Oocytes were incubated for 3 h with 10 mM nitrate, pH 5.5, and nitrate retained in the oocyte was measured by HPLC.…”
Section: The Pericycle Cells Close To the Protoxylem Play A Special Rmentioning
confidence: 99%